2018
DOI: 10.3390/ijms19113370
|View full text |Cite
|
Sign up to set email alerts
|

Integration between ROS Regulatory Systems and Other Signals in the Regulation of Various Types of Heat Responses in Plants

Abstract: Because of their sessile lifestyle, plants cannot escape from heat stress and are forced to alter their cellular state to prevent damage. Plants, therefore, evolved complex mechanisms to adapt to irregular increases in temperature in the natural environment. In addition to the ability to adapt to an abrupt increase in temperature, plants possess strategies to reprogram their cellular state during pre-exposure to sublethal heat stress so that they are able to survive under subsequent severe heat stress. Such an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 146 publications
(281 reference statements)
2
46
0
Order By: Relevance
“…Previous studies revealed that crosstalk between Ca 2+ , O 2 − and NO signaling regulates multiple processes of reproductive development (Katano et al, 2018a; Prado et al, 2004; Serrano et al, 2015; Traverso et al, 2013). We therefore analyzed the distribution and accumulation of Ca 2+ , O 2 − and NO in flowers with poor or rich pollen attachments (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that crosstalk between Ca 2+ , O 2 − and NO signaling regulates multiple processes of reproductive development (Katano et al, 2018a; Prado et al, 2004; Serrano et al, 2015; Traverso et al, 2013). We therefore analyzed the distribution and accumulation of Ca 2+ , O 2 − and NO in flowers with poor or rich pollen attachments (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon might be involved in pollen recognition. In addition, during the pollen attachment on stigma, antioxidant substance in pollen coat was released into stigma via pollen hydration induced by NO-ROS redox signals (Katano et al, 2018a; Traverso et al, 2013). As for stigma with pollens, Ca 2+ accumulated in pollens and clearly increased in stigma, suggesting that high accumulation of Ca 2+ might be caused by activation of calcium permeable channel via NO derived from pollen (Besson-Bard et al, 2008; Clementi, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic signaling from local to systemic tissues was demonstrated for many types of stresses including abiotic conditions, such as light stress, mechanical stress and temperature stress, as well as biotic stresses, such as bacterial, fungal and viral infections (e.g. Guerra et al , ; Choi et al , ; Katano et al , ; Lai et al , ; Chen et al , ). The faster the systemic response is, the better chance the plant has to acclimate and defend itself against the upcoming abiotic or biotic challenge (Kollist et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we can expect that decrease in seed production caused by heat stress might be also at least partially attributed to morphological alterations in reproductive organs (De Storme and Geelen, 2014). Although the research of heat stress response in reproductive organs have progressed from the view point of molecular biology and physiology (Katano et al, 2018a;Suzuki and Katano, 2018), only few studies have focused on morphological alterations of reproductive organs caused by heat stress (De Storme and Geelen, 2014).…”
Section: Introductionmentioning
confidence: 99%